Inspection of Leveling and Verticality of Silo Foundations Due to Settlement Based on SNI 8460: 2017 - Citra, Zel; Gede Ananda Kusuma, I Dewa; Adistana, Herlis Sweta; Lumingkewas, Riana Herlina; Haifan, Mohamad (CIVED, 2024)
The foundation is the most essential structural element of a building structure. A solid and stable foundation is a critical factor in ensuring the sustainability and safety of a building. Proper planning and calculations are essential in designing the foundation to withstand the structural loads from the building above it and ensure that the foundation does not experience dangerous settlement or collapse. In this research, the author conducted a study or examination of the condition of Silo Foundation PT XYZ is located in the Tangerang. The number of silo foundations built was 7 units (silo 17, silo 18, silo 19, silo 20, silo 21, silo 22 and silo 23). This silo is a vertical storage structure that functions as a place to store raw materials for animal feed. The condition of the silo foundation structure is known to have decreased after being filled to a maximum capacity of 5000T. To determine the condition of the foundation structure, it is necessary to carry out a measurement survey by checking levelling and verticality using reference standards or rules used by SNI 8640:2017. The results of foundation levelling tests for silo 17, silo 18, silo 19, silo 20, silo 21, silo 22 and silo 23 in Balaraja District, Tangerang Regency, there is the most significant elevation difference occurring at silo 19, namely 127 mm, which is based on SNI Geotechnical 8460-2017 Maximum building settlement is included in High Risk because the settlement is > 75 mm. The elevation differences in the other silos fall into the Small Risk to Medium Risk categories. Meanwhile, based on the results of checking verticality, it was found that the slope value of the structure in Silos 18, 19 and 21 experienced a slope that exceeded the maximum required permit limit of 20mm. Therefore, it is necessary to carry out regular inspections to monitor the movement or decline of the silo foundation so as not to cause risks or conditions of structural failure.